Low-Income Turkish Mothers’ Conceptions and Experiences of Family Life - Erdem, Gizem; Adli-Isleyen, Merve; Baltalarlı, Nur; Kılıç, Ezgi (Frontiers in Psychology, 2022)
The current qualitative study explores women's conceptions of the normative family and their day-to-day family lives. To that aim, we conducted five focus group interviews in two low-income neighborhoods of Istanbul. The sample included 43 women (42 biological mothers and a grandmother) who had at least one child between ages 3 and 8 in their care. Participants were 35.64 years old on average (SD = 4.74) and were all married. Women had approximately two children on average (SD = .72) whose mean age was 7.92 years old (SD = 3.11). Each focus group was semi-structured, lasted for 1-1.5 hours, and included 5 to 12 participants. Thematic analysis of the focus group interview data, moderator memos, and observer's notes revealed five defining features of healthy family functioning: cohesion, healthy child, parenting, conflict, control, and family organization. Overall, women prioritized motherhood over their other social identities and idealized the happy family, which contradicted their actual lived experiences in the family system. We discuss how women’s depictions of all family processes revolved around cultural constructs of gender, socio-economic status, and independence/interdependence. The findings of this study shed light on future interventions for low-income women and their families in Turkey.